Bacterial canker of stone fruit trees caused by Pseudomonas syringae pv. syringae and P. syringae pv. morsprunorum : numerical analysis of phenotypic features of the pathogens ... - Roos, Isabel M. M (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D. Agric.) -- University of Stellenbosch, 1986.